An intelligent tumor microenvironment responsive nanotheranostic agent for T1/T2 dual-modal magnetic resonance imaging-guided and self-augmented photothermal therapy. (20th October 2021) - Yao, Junlie; Zheng, Fang; Yang, Fang; Yao, Chenyang; Xing, Jie; Li, Zihou; Sun, Sijia; Chen, Jia; Xu, Xiawei; Cao, Yi; Hampp, Norbert; Wu, Aiguo
Abstract : Engineering Zn0.2 Fe2.8 O4 @PDA@MnO2 nanosystem for T 1/ T 2 dual-modal magnetic resonance imaging-guided and self-augmented photothermal therapy. Abstract : Photothermal therapy (PTT), as a promising antineoplastic therapeutic strategy, has been harnessed to restrain tumor growth through near-infrared (NIR) irradiation mediated thermal ablation. Nevertheless, its biological applications are hampered by thermal diffusion and up-regulated heat shock proteins (HSPs). Herein, a versatile nanotheranostic agent is developed via integrating Zn0.2 Fe2.8 O4 nanoparticles (NPs), polydopamine (PDA), and MnO2 NPs for T 1/ T 2 dual-modal magnetic resonance (MR) imaging-guided and self-augmented PTT. The as-designed Zn0.2 Fe2.8 O4 @PDA@MnO2 NPs adequately serve as a PTT agent to realize effective photothermal conversion and obtain local hyperthermia. Additionally, the Zn0.2 Fe2.8 O4 @PDA@MnO2 NPs can significantly consume overexpressed glutathione (GSH) and generate Mn 2+ in the tumor microenvironment (TME), thus destroying redox homeostasis and catalytically generating hydroxyl radicals (˙OH) for HSP suppression and PTT enhancement. Meanwhile, Mn 2+ and Zn0.2 Fe2.8 O4 NPs significantly strengthen T1- and T2-weighted MR contrast for tumor imaging and PTT guidance. Hence, this study offers proof of concept for self-augmented PTT and T 1/ T 2 dual-modal MR imaging for tumor elimination.